Konstruktion och undersökelse, exotism och närhet i Per Olof Sundmans böker om Lofoten - Bourguignon, Annie (Nordlit, 2007)
The Swedish writer Per Olof Sundman (1922-1992) wrote mostly short stories and novels, but also reportages. The paper deals with two reportages from the Lofoten islands, Människor vid hav (1966, “People by the sea”) and Lofoten, sommar (1973, “Lofoten, summer”) The choice of the Lofoten islands as a subject is related to a fascination Sundman felt towards northern and arctic regions, a fascination he also expressed in a number of fictional narratives and in the documentary novel Ingenjör Andrées luftfärd (1967. English title: The Flight of the Eagle) A question that arises almost immediately is whether that fascination affects the way the reporter works and how it affects it. How does Sundman look at the Lofoten? What does he take notice of and tell us about? What kind of image does he give? And how does he understand his own role, his function as an investigator in an environment which is neither his own nor his postulated readers’ usual environment? Another question deals with the relationship between the reportages from the Lofoten and the author’s other works. Are the reportages easy to recognize as Sundmanian texts, can Sundman’s “signature” be traced in them? It appears that “People by the sea” and “Lofoten, summer” are not merely informative texts. They also to a rather high degree suggest an atmosphere, using among other things inherited representations and judgements to that purpose. Those reportages turn out to be strongly literary texts, in the traditional meaning of the word.